Hemocyanin facilitates lignocellulose digestion by wood-boring marine crustaceans - Katrin Besser (Nature Portfolio, 2018)
Marine woodborers can digest woody biomass without the help of gut microbiota but the mechanism has remained unclear. Here, the authors provide evidence that the woodborer’s respiratory protein hemocyanin plays a central role in wood digestion and may offer a route toward biorefining of woody plant biomass.